Implementation of the Macao dementia policy: a scoping review for the way forward - Tang, Pou Kuan; Cen, Zhifeng; Zheng, Yu; Shi, Junnan; Hu, Hao; Ung, Carolina Oi Lam (Frontiers in Public Health, 2024)
Background The implementation of dementia policy is a complex process of translating policy goals to actions to address the changing needs of people living with dementia. Leveraging on others’ experiences would help policy decision-makers and actors better prepare for the challenges. Purpose This study explored the development, the implementation and the impact of the dementia policy in Macao, a “role model” recognized by the Alzheimer’s Disease International. Methods A scoping review of policies, strategies, and news articles, as well as scholarly work from 6 scientific databases dated till March 2023 was conducted under the guidance of the Health Policy Triangle Framework. Results According to 284 documents, the dementia policy in Macao, driven by government leadership and supported with public-private partnership, aimed to integrate health and social services to achieve the goals of “Early prevention, Early detection, Early diagnosis, Early treatment and Early support.” Promoting the preparedness according to the dementia burden trajectory, empowering the public and the service providers with training and education, and encouraging services-related research were among the key actions. With major changes in dementia care configuration, a dementia service network, a dementia-friendly community and a one-stop service model for disease screening, diagnosis, treatment and support have been developed. Discussion Reconfiguring existing resources in the health and social services to form an integrated service network at the community level could be considered a priority of action. Continuous engagement, collaboration and empowerment at different levels across these sectors is crucial for the sustainability of a dementia policy.